The need to constitutionalise the National Electoral Commission – selected issues (Discourse of Law and Administration, 2023)
The author analyzed the legitimacy of the constitutionalisation of the State Commission.The observation of the activities of the democratic state institutions made us reflect once again onthe need or even justifiability of assigning the status of a constitutional body to the NEC. The conclusionof the considerations introduces the postulate to raise to the rank of constitutional StateElectoral Commission, which is an organ of state control and protection of the law. The constitutionalfoundation is extremely important for the structure and composition of the electoral bodies.The analysis of the tasks of the NEC proves that the constitutionalization of this central electoralbody, supervising the implementation of passive and active electoral law, and of a body independentof the executive, seems to be necessary in the light of its current competences.
Keywords: election administration; election law; administrative law